Lowest Oxyhemoglobin Saturation May Be an Independent Factor Influencing Auditory Function in Severe Obstructive Sleep Apnea - Seo, Young Joon (J Clin Sleep Med, 2016)
STUDY OBJECTIVES: The aims of this study were to determine if a correlation exists between the level of hypoxia induced by severe obstructive sleep apnea syndrome (OSAS) and the level of auditory dysfunction when verifying such a relationship using polysomnography (PSG). METHODS: A retrospective review of 41 patients with severe OSAS was performed. Independent risk factors for hearing impairment included parameters of PSG, which were analyzed in two hearing groups at a level ≥ 40 decibels (dB). RESULTS: Oxyhemoglobin saturation, especially the lowest oxyhemoglobin saturation level, showed lower thresholds in the hearing impairment group than in the control group (p = 0.039 at NREM stage; p = 0.029 at REM stage; p = 0.001 at total sleep stage). After adjusting for other risk factors, the sole variable that remained significant was lowest oxyhemoglobin saturation (total; p = 0.046). In the correlation analysis, a decreasing lowest oxyhemoglobin saturation (from all subjects, n = 41) correlated with a greater mean hearing threshold (R(2) = 0.297; p < 0.001). CONCLUSION: Our results indicated that lowest oxyhemoglobin saturation in PSG is the only variable correlated with the hearing threshold. This finding could be predictive of possible hearing alternation in patients with severe OSAS. COMMENTARY: A commentary on this article appears in this issue on page 641. CITATION: Seo YJ, Park SY, Chung HJ, Kim CH, Lee JG, Kim SH, Cho HJ. Lowest oxyhemoglobin saturation may be an independent factor influencing auditory function in severe obstructive sleep apnea. J Clin Sleep Med 2016;12(5):653–658.